2021
DOI: 10.3390/ijms22136753
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Three Drug-Based Therapy for Neuroblastoma in Mice

Abstract: High-risk neuroblastoma (HR-NB) still remains the most dangerous tumor in early childhood. For this reason, the identification of new therapeutic approaches is of fundamental importance. Recently, we combined the conventional pharmacological approach to NB, represented by cisplatin, with fendiline hydrochloride, an inhibitor of several transporters involved in multidrug resistance of cancer cells, which demonstrated an enhancement of the ability of cisplatin to induce apoptosis. In this work, we co-administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Neuroblastoma exhibits a wide range of clinical behaviors, with some tumors undergoing spontaneous regression, whereas others follow an aggressive course. Extensive research has been conducted on this childhood cancer, including studies on infant screening, stem cell transplantation, prognostic genes, drug-based treatments, and DNA methylation fingerprints [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma exhibits a wide range of clinical behaviors, with some tumors undergoing spontaneous regression, whereas others follow an aggressive course. Extensive research has been conducted on this childhood cancer, including studies on infant screening, stem cell transplantation, prognostic genes, drug-based treatments, and DNA methylation fingerprints [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of diclofenac in combination therapy with cisplatin significantly increases ROS-induced macroautophagy [ 10 ]. Aiming to improve the cancer pharmacological approach, a pilot study demonstrated, in a neuroblastoma xenograft model, the strengthening of cisplatin effects when administered as cocktail therapy with acetazolamide, a carbonic anhydrase isoform IX inhibitor, and fendiline hydrochloride, an inhibitor of several transporters involved in multidrug resistance of cancer cells [ 11 ].…”
mentioning
confidence: 99%